SOSIALISASI TEKNOLOGI DALAM PEMBELAJARAN BAHASA UNTUK MENINGKATKAN LITERASI MEDIA PEMBELAJARAN DIGITAL GURU SD - Dewi Surani; Rini Dwi Septiyani; Octavia Saptala; Ananda Nida Syifaturahamah (Jurnal Abdimas Bina Bangsa, 2024)
Community service carried out with educational methods to elementary school teachers in thr form of training. The training is about technology in language learning in improving literacy as a learning medium. The activity was held at SDN 1 Ciemas, Desa Sukawana, Kecamatan Curug, Kota Serang with 10 participants. The prospective participants involved included all elementary school teachers. Preparations were carried out starting from preparing supporting documents for activities, such as requests for letters of assignment, as well as coordination with prospective service participants through school leaders. At the implementation stage, this service took place face-to-face and was facilitated by the school. The speaker provides material according to the topic of discussion. The training is carried out interactively, there are questions and answers and direct practice carried out by the trainees and guided by the speaker. After the training ended, an evaluation was conducted. Starting from the preparation stage, the course of activities, and the response of participants during the training activities. The participants in the school still need to develop language learning media using technology